Concentrations of and risks posed by short-chain and medium-chain chlorinated paraffins in soil at a chemical industrial park on the southeast coast of China. (March 2020) - Huang, Di; Gao, Lirong; Qiao, Lin; Cui, Lili; Xu, Chi; Wang, Kunran; Zheng, Minghui
Abstract: The concentrations, spatial distributions, and sources of short-chain chlorinated paraffins (SCCPs) and medium-chain chlorinated paraffins (MCCPs) in soil at a chemical industrial park were determined. The samples were analyzed by two-dimensional gas chromatography coupled with electron capture-negative ion mass spectrometry. The risks posed by SCCPs and MCCPs to soil biota were assessed. The SCCP and MCCP concentrations were 37.5–995.7 and 15.1–739.6 ng/g dry weight, respectively, and the chlorine contents were 60.5%–63.0% and 56.7%–58.3%, respectively. The CP concentrations in soil were at medium levels relative to concentrations at other areas. The median CP concentration in soil from the sewage treatment plant was higher than the median concentration in road soil, and this was attributed to wastewater being treated centrally. No significant correlations were found between the total organic carbon content and CP concentrations (p > 0.05), so the total organic carbon content did not strongly affect the CP concentrations in the study area. Hierarchical cluster analysis divided the soil samples into three groups. C10 Cl6–7, C11 Cl7–8, and C14 Cl7–9 were the main congeners in most soil samples. Principal component analysis and correlation analysis indicated that the relative abundances of MCCP and SCCP were correlated and that the SCCPs may have been derived from the CP-42 and CP-52 commercial products. A preliminary risk assessment indicated that CPs in soil at the industrial park do not pose clear risks to the environmental organisms. Graphical abstract: Image 1 Highlights: SCCP and MCCP concentrations in soil at a chemical industrial park were determined. Medium concentrations were found, indicating CPs may not have been released directly. Industrial/other activities and the environment affected CP spatial distributions. CPs at the site do not pose clear risks to environmental organisms. Abstract : This study determined the occurrences and homolog patterns of CPs in soil of a typical chemical industry park, indicating that industrial/other activities affected CP spatial distributions.